Alpha-tocopherol concentration in serum and colostrum of mothers with gestational diabetes mellitus - Resende,Fernanda Barros S. (2014)
OBJECTIVE: To evaluate and compare the levels of α-tocopherol in colostrum and in the serum of healthy and diabetic mothers.METHODS: This cross-sectional study enrolled 51 volunteer mothers, 20 with the diagnosis of gestational diabetes mellitus and 31 without associated diseases. Serum and colostrum samples were collected in fasting in the immediate postpartum period and α-tocopherol was analyzed by high performance liquid chromatography (HPLC). In order to define the nutritional status of vitamin E, the cutoff point for the serum (697.7µg/dL) was adopted. Student's t-test for independent variables compared the average concentrations of α-tocopherol in the serum and in the colostrum between control and gestational diabetes mellitus groups. Pearson's correlation was used to assess the relationship between the concentration of α-tocopherol in serum and colostrum for both groups. Differences were considered significant when p<0.05.RESULTS: The α-tocopherol concentration in colostrum was 1,483.1±533.8µg/dL for Control Group and 1,368.8±681.8µg/dL for diabetic women, without differences between groups (p=0.50). However, α-tocopherol concentration in the serum was 1,059.5±372.7µg/dL in the Control Group and 1,391.4±531.5µg/dL in the diabetic one (p<0.01). No correlation was found between the concentration of α-tocopherol in the serum and in the colostrum for control and diabetic groups.CONCLUSIONS: The groups had adequate nutritional status of vitamin E. Gestational diabetes was not associated with changes in α-tocopherol concentration in colostrum.